Inhibitors of Complement Activity in Human Breast-Milk: A Proposed Hypothesis of Their Physiological Significance - Michael Oladipo Ogundele (Mediators of Inflammation)
Several natural components abundant in the fluid phase of human breast-milk have been shown to be inhibitors of complement activation in vitro, particularly the classical pathway. These include lysozyme, lactoferrin, lactalbumin alpha and other ligand chelators, complement regulator proteins and other specific soluble inhibitors of complement activation. Their physiological significance probably resides in their ability to restrict in vivo complement activation to specialized (compartmentalized) sites on the cellular membrane structures in human milk, represented by the abundant surface area of the milk fat globule membranes. This would serve to prevent inflammatory-induced tissue damage of the delicate immature gastrointestinal tract of the newborn as well as the mammary gland itself. A number of recognized and potential inhibitors of complement activity in human milk and other biological fluids are hereby reviewed, with a proposal of their physiological significance.